Role of the styles of creative behavior in the etiology of students burnout - Strzałecki, Andrzej; Kabala, Agata (Studia Psychologica: Theoria et praxis, 2007)
Senior’s author model of The Style of Creative Behavior, operationally defined by the „The Creative Behavior Questionnaire”, was used to study the etiology of students burnout. A new Students Burnout Inventory (SBI) was constructed and analyzed by means of factor analysis which revealed five factors: 1. Physical exhaustion; 2. Psychological exhaustion; 3. Emotional exhaustion; 4. Low motivation; 5. Apathy. The regression analysis revealed that the most important role in the students burnout is plaid by the low scores in The Strength of ego and Self-realization. The multiple R of these traits with the general score of the SBI is 0,70 and explains 49% of variance ((F2, 65=30,81, p<0,001)). The article ends the discussion of the role of creativity in students personality integration, their well-being and success in the studies.